Does Coordination Flexibility Mediates the Relationship Between Strategic Orientation and Innovative Performance? - Vem, Linus Jonathan; Samson, Nancwat; Nkup, Yilshian Noel; Idi Jamoke, Arandong (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2022)
The current global events have posed a great challenge to the survival of SMEs. This study is motivated to identify the factors that enhance innovative performance among SMEs by exploring the path of Strategic orientation (SO) and coordination flexibility (CF). A total of 400 copies of the structured questionnaire was administered to top managers and Supervisors in Nigeria. Out of the 400 copies administered to top managers, 200 were completed, while 217 were completed and returned by the supervisors out of 400 administered to them as well. Partial Least Square (PLS) software 3.3.3, a variance-based Structural Equation Modelling was used to analyse the data. The results indicate that SO, CF in employee skill but not HR practice was found to relate significantly with IP as well as mediate the relationship with SO. Thus, we concluded that IP can be enhanced through SO and explained through CF in employee skills.